Peningkatan Kewaspadaan Warga Terhadap Banjir Melalui Penerapan Alat Pemantau Ketinggian Air di Aliran Sungai Kalijompo Kabupaten Jember - Ali Rizal Chaidir; Satryo Budi Utomo; Gusfan Halik; Gamma Aditya Rahardi Rahardi; Kurniawan Hidayat (Sam Ratulangi University, 2023)
Flooding is a natural phenomenon that occurs as a result of high rainfall resulting in excess water that is not accommodated by the system. In general, the impact of floods can be detrimental to the community, especially people who live on the outskirts of the river. Jember Regency is one of the regencies that has many rivers that have the potential to not be able to accommodate water in the rainy season, resulting in flooding, one of which is the Kalijompo River, which floods almost every year. The impact of flooding can be minimized with good development and an early warning system for residents. Technology is one way to make human work easier, one of which is to monitor a situation. The application of river flow monitoring technology can reduce the detrimental impact of flooding. This technology provides information to residents about water levels. The technology applied has sensors that can monitor the height of the river flow, the height of the river flow consists of four levels, namely normal to dangerous which is marked by an alarm sound, so that when a flood occurs at night residents can get up immediately to save themselves, then the detrimental impact of flooding can be reduced.